Prevalence of Liver Cancer in Isfahan Province, Iran - Ghamari, Zahra Tolou; Tadayon, Farhad; Mazdak, Hamid (Indonesian Journal of Cancer, 2018)
Background: Liver cancer remains to grow worldwide. We aimed to describe the period prevalence (PP) and incidence rates (Irs) for liver cancer in Isfahan Province that is located in the center of Iran and ranked as the third province in terms of population.Methods: Information related to the Surveillance, Epidemiology, and End Results; (SEER) was collected from the Isfahan Cancer Registry. Period prevalence (PP) was calculated per 100,000 people. The cancer sites studied were defined according to the International Classification of Diseases (ICD-O; Third Edition) and recorded by topography code (C22).Result: Among all registered liver cancer patients, 57% of the 920 cases were male. The mean age of the patients was 65.9 ± 16.8 years. Reported age in 13% of the patients was less than 50 years and as high as 84% were in between 50 to 90 years. With a total PP of 18.5 per 100,000 people, this value was 24.4% higher in males when compared to females (16.8 vs. 20.9). In the previous years, incidences were 3.9 (2011-2012), 5.3 (2012-2013), 4.9 (2013-2014) and 4.2 (2014-2015) per 100,000 people. There were 89% reported deaths among the total population.Conclusion: The PP for liver cancer in male population was approximately 24.4% higher than females. There was a 7.7% increase in the Irs over the study period. Further study toward estimation of the proportion of the causes of liver cancer and deaths due to infection of hepatitis B and C virus, exposure to aflatoxin, alcohol drinking and smoking seem to be advantageous. Therefore, the plan of healthcare system should focus on greater effort toward strategic evidence-based pharmacotherapy in Isfahan province/Iran.